Impact of admission serum ionized calcium levels on risk of acute kidney injury in hospitalized patients - Thongprayoon, Charat (Sci Rep, 2020)
This study aimed to investigate the risk of acute kidney injury (AKI) in hospitalized patients based on admission serum ionized calcium levels. This is a cohort study of all hospitalized adult patients, from January 2009 to December 2013 at a tertiary referral hospital, who had available serum ionized calcium at the time of admission. We excluded patients who had end-stage kidney disease or AKI at admission. We stratified admission serum ionized calcium into 6 groups; ≤ 4.39, 4.40–4.59, 4.60–4.79, 4.80–4.99, 5.00–5.19, and ≥ 5.20 mg/dL. We used serum creatinine criterion of KDIGO definition for diagnosis of AKI. We performed logistic regression analysis to assess the risk of in-hospital AKI occurrence based on admission serum ionized calcium, using serum ionized calcium of 5.00–5.19 mg/dL as the reference group. We studied a total of 25,844 hospitalized patients. Of these, 3,294 (12.7%) developed AKI in hospital, and 622 (2.4%) had AKI stage 2 or 3. We observed a U-shaped association between admission serum ionized calcium and in-hospital AKI, with nadir in-hospital AKI was in serum ionized calcium of 5.00–5.19 mg/dL. After adjustment for confounders, low serum ionized calcium of 4.40–4.59, ≤ 4.39 mg/dL and elevated serum ionized calcium ≥ 5.20 mg/dL were associated with increased risk of AKI with odds ratio of 1.33 (95% CI 1.14–1.56), 1.45 (95% CI 1.21–1.74), and 1.26 (95% CI 1.04–1.54), respectively. Both hypocalcemia, and hypercalcemia at the time of admission were associated with an increased risk of hospital-acquired AKI.